Factors Associated with Fluoride Concentrations in Whole and Parotid Ductal Saliva - Fukushima, R.; Pessan, Juliano Pelim [UNESP]; Sampaio, F. C.; Buzalaf, M. A. R. (Karger, 2011)
Background/Aims: There are still uncertainties regarding the use of whole and parotid ductal saliva as indicators of chronic exposure to fluoride. This study evaluated the effect of water fluoride concentration, age, gender, geographical area and localization (urban/rural) on fluoride concentrations in whole and ductal saliva. Methods: Subjects (n = 300) aged 3-7, 14-20, 30-40 and 50-60 years, from five communities (A-E) with different fluoride concentrations in the drinking water, participated in the study. Two samples of drinking water and parotid and whole saliva were collected for each subject and were analyzed for fluoride using appropriate electrode techniques. Results: Mean water F concentrations (+/- SE, mg/l, n = 60) were 0.09 +/- 0.01, 0.15 +/- 0.01, 0.66 +/- 0.01, 0.72 +/- 0.02, and 1.68 +/- 0.08 for A-E, respectively. Mean F concentrations (+/- SE, mg/l, n = 15) ranged between 0.014 +/- 0.002 (A, 3-7 years) and 0.297 +/- 0.057 (D, 14-20 years) for whole saliva and 0.009 +/- 0.001 (C, 30-40 years) and 0.284 +/- 0.038 (E, 50-60 years) for parotid saliva. Results of multivariate linear regression analysis showed that geographical area and water fluoride concentration exerted the strongest influence in whole and ductal saliva F concentrations, respectively. Conclusion: Therefore, parotid ductal saliva seems to be a more appropriate biomarker of fluoride exposure, and factors like age and localization should also be considered when using this biomarker. Copyright (C) 2011 S. Karger AG, Basel
Keywords: Biological markers; Drinking water; Fluoride; Saliva